2008
DOI: 10.1097/qad.0b013e3282faa71e
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of adverse events in healthy volunteers receiving rifampicin and adjusted doses of lopinavir/ritonavir tablets

Abstract: The study showed a high incidence of adverse events when a higher than standard dose of the new lopinavir/ritonavir tablets was combined with rifampicin. In the future, this drug combination should not be given to healthy volunteers. Liver function should be carefully monitored when rifampicin and lopinavir/ritonavir are combined in patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
66
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 19 publications
5
66
2
Order By: Relevance
“…These safety findings were attributed to efavirenz, a CYP3A inducer, as coadministration of the 3D regimen with emtricitabine and tenofovir DF was well tolerated in healthy volunteers. Similar safety findings were observed when the CYP3A inducer rifampin or efavirenz was coadministered with ritonavir-boosted protease inhibitors such as lopinavir and saquinavir in healthy volunteers (28)(29)(30). Patients treated with these therapy combinations reported AEs consistent with our observations, including abdominal symptoms and transaminase elevations.…”
Section: Discussionsupporting
confidence: 88%
“…These safety findings were attributed to efavirenz, a CYP3A inducer, as coadministration of the 3D regimen with emtricitabine and tenofovir DF was well tolerated in healthy volunteers. Similar safety findings were observed when the CYP3A inducer rifampin or efavirenz was coadministered with ritonavir-boosted protease inhibitors such as lopinavir and saquinavir in healthy volunteers (28)(29)(30). Patients treated with these therapy combinations reported AEs consistent with our observations, including abdominal symptoms and transaminase elevations.…”
Section: Discussionsupporting
confidence: 88%
“…These high rates of hepatotoxicity in healthy volunteers might not apply to patients with tuberculosis and HIV. First, in the healthy-volunteer studies, initiating rifampin prior to the protease inhibitor was associated with high rates of hepatotoxicity (6,7,16). In high-burden countries, protease inhibitors are used as part of the second-line antiretroviral treatment (ART) regimen; hence, most patients are established on the protease inhibitor before rifampin is initiated.…”
mentioning
confidence: 99%
“…Subsequent healthy-volunteer studies of the interaction between rifampin and adjusted doses of ritonavir-boosted saquinavir, atazanavir, and lopinavir (tablet formulation) were prematurely terminated because of high incidences of hepatotoxicity (6,7,16). These high rates of hepatotoxicity in healthy volunteers might not apply to patients with tuberculosis and HIV.…”
mentioning
confidence: 99%
“…However, high rates of elevated transaminases, lipid changes and gastrointestinal toxicity were observed [187]. A pharmacokinetic study in healthy volunteers of such a strategy was terminated early because of high rates of severe increase of liver enzymes/transaminases [188]. Another strategy is to double the dose of lopinavir/ritonavir which also overcomes the effect of rifampicin induction [187].…”
Section: Lopinavir/ritonavirmentioning
confidence: 99%
“…This is done by either adding high-dose ritonavir (additional 300 mg every 12 h) to lopinavir/ritonavir combination or by doubling the lopinavir/ritonavir dose to overcome the induction by rifampicin. In healthy volunteer and patient studies, high rates of hepatic events and gastro-intestinal intolerance have been reported with such strategies and patients should be carefully monitored for the development of jaundice or hepatitis [188,198]. Quadruple nucleosides are also a possibility as ART.…”
Section: Pi and Rifamycins: What To Do?mentioning
confidence: 99%